Formal driven prototyping approach for multiagent systems. (28th February 2008) - Hilaire, Vincent; Gruer, Pablo; Koukam, Abderrafiaa; Simonin, Olivier
Even if Multiagent Systems (MASs) are recognised as an appealing paradigm for designing many computer systems ranging from complex distributed systems to intelligent software applications, they are still difficult to engineer. A common point of MAS engineering methodologies is the production of different work products or models during the different phases. Each work product or model helps to progress towards an implementation of the system under development. Nevertheless, there are very few ways to ensure that the work products and models produced are validated against the requirements. The aim of this paper is to present a formal driven prototyping approach for MAS. This process provides a support for incremental specification leading to an executable model of the system being built. Indeed, this process is based upon a formal organisational framework which uses a formal notation, namely OZS. The process is illustrated through the specification of a multiagent architecture.